Perancangan Sistem Informasi Pemantauan Isolasi Mandiri Pada Karyawan Penderita Covid-19 Berbasis Website Menggunakan Metode Rapid Application Development (Studi Kasus : PT.MMS Group Indonesia) - Triyono; Achmad Lutfi Fuadi (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Coronavirus 2019 (Covid-19) is a dangerous infectious disease that was first detected in Wuhan, the capital of Hubei Province in China, in December 2019 and has since spread worldwide. Preventive efforts are being made to stop and stop the spread of Covid-19 patients, both symptomatic and asymptomatic. Employee monitoring using Covid-19 is now done by sending health data to the company's Covid-19 task force via the Whatsapp application and transferring the records to Microsoft Excel for use as a report to the company's management. In reality, this is very time consuming and often results in recording errors, resulting in errors and delays in submitting reports to senior management. In addition, self-isolated Covid-19 employees will not be able to receive health counselling with doctors who have worked for the company. Rapid Application Development (RAD) methods are system development processes that focus on the speed of development by actively and repeatedly engaging users in each development process to meet their needs through modelling. Easy to develop. To overcome these issues, the aim was to facilitate the work of the Covid-19 Task Force, which monitors the health of people affected by Covid-19, manages data, and submits reports to company management.